Funkcja profilaktyczna edukacyjnych gier komputerowych - Polcyn , Sylwia (Kultura-Społeczeństwo-Edukacja, 2018)
Polcyn Sylwia, Funkcja profilaktyczna edukacyjnych gier komputerowych [The prophylactic function of educational video games]. Kultura – Społeczeństwo – Edukacja nr 2(14) 2018, Poznań 2018, pp. 127–135, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2018.14.11. The article presents a modern look at computer games as tools and / or teaching aids used for broadly understood educational and didactic purposes at various levels of education. The author focuses mainly on the use of computer games for prophylactic purposes, and especially in counteracting various negative phenomena occurring in cyberspace.